Evaluation of anti-tubercular activity of leaves of vitexnegundo by in –vitro method (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
One third of the world’s population is thought to be infected with tuberculosis. As the searches are going on anti-tubercular natural flavonoids. The leaves of Vitexnegundowere found to be rich in phytochemical constituents with may have immense pharmacological actions. The literature survey revealed the presences of alkaloids, glycosides, flavonoids, tannins, steroids and  terpenoids, carbohydrates, proteins  in the entire plant in which flavonoids are responsible for anti-tubercular activity. The results of the present study  indicates that different extracts of leaves of Vitexnegundo exhibited anti-tubercular activity against M.tuberculosis (H37RV Strain) at the doses of 100µg/ml and 50 µg/ml shows the inhibition of growth among all 8 concentrations such as 0.8,1.6,3.12,6.25,12.5,25,50,100 µg/ml by using Alamar blue assay method for in-vitro evaluation of anti-tubercular activity.